Lost science: a Latin American debate - Luis Ernesto Paz Enrique (Medisur)
This contribution analyzes the ways in which science is constructed in Latin America and the Caribbean. Its main objective is to highlight the particularities of this region and how these differences affect scientific development compared to other areas of the world, from the lost and invisible science’s perspective. It is argued that science in Latin America and the Caribbean has developed mainly through collaboration and cooperation between countries, but its scientific journals are at a disadvantage due to globalized science that limits access to local topics. This approach has been driven by the need to overcome the economic and technological limitations present in the region. As a result, own initiatives have been created that highlight the importance of contributions and local knowledge in the construction of science. Having its own and contextualized perspective is essential to address the specific challenges and needs of the region. This is reflected in the diversity of research topics and scientific approaches. The article also mentions some of the challenges and obstacles faced by science in Latin America and the Caribbean, despite which the resilience and creativity of Latin American and Caribbean scientists stands out, who have managed to make significant contributions worldwide.